Measurement of the CP-violating phase [phi]s in B[Oberstrich]0s → J/[psipi]+[pi]- decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2014)
The mixing-induced CP-violating phase ϕs in Bs0 and B¯s0 decays is measured using the J/ψπ+π− final state in data, taken from 3 fb−1 of integrated luminosity, collected with the LHCb detector in 7 and 8 TeV centre-of-mass pp collisions at the LHC. A time-dependent flavour-tagged amplitude analysis, allowing for direct CP violation, yields a value for the phase ϕs=70±68±8 mrad. This result is consistent with the Standard Model expectation and previous measurements.